KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS TLOGOSARI KULON KECAMATAN PEDURUNGAN (STUDI KASUS PADA BAGIAN FARMASI) - Akhmad Syarif Hidayatullah; Ida Hayu Dwimawanti; Tri Yuniningsih (Journal of Public Policy and Management Review, 2023)
Service quality is one measure to assess public services. Pharmaceutical services at the puskesmas are an integral part of the implementation of health efforts, which play an important role in improving the quality of health services for the community. However, in the process of implementing health services at the Pharmacy Section of the Tlogosari Kulon Health Center, Pedurungan District, it has not gone well. This study uses a descriptive research method with a qualitative approach. The purpose of this study was to analyze the quality of health services at the Pharmacy Section of the Tlogosari Kulon Health Center, Pedurungan District and the inhibiting factors. The theory used by researchers is the theory of service quality according to Zeithaml, Parasuraman, and Berry. The results of the study revealed that the quality of health services at the Pharmacy Section of the Tlogosari Kulon Health Center, Pedurungan District, had not run optimally. As for the inhibiting factors that influence such as awareness factors, factor systems of rules or procedures, factor of service facilities. Researchers recommend developing and updating service facilities and infrastructure in order to encourage good health services at the Pharmacy Section of the Tlogosari Kulon Health Center, Pedurungan District